2014
DOI: 10.1007/s10900-014-9932-9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Hepatitis C Testing and Linkage to Care for Vulnerable Populations: Point-of-Care and Standard HCV Testing in a Mobile Medical Clinic

Abstract: Despite new Hepatitis C virus (HCV) therapeutic advances, challenges remain for HCV testing and linking patients to care. A point-of-care (POC) HCV antibody testing strategy was compared to traditional serological testing to determine patient preferences for type of testing and linkage to treatment in an innovative mobile medical clinic (MMC). From 2012 to 2013, all 1,345 MMC clients in New Haven, CT underwent a routine health assessment, including for HCV. Based on patient preferences, clients could select be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 57 publications
5
61
0
Order By: Relevance
“…The remaining 6 screening-related interventions (Table 1) demonstrate high rates of uptake and case-finding when interventions target high-risk individuals in specific settings, including PWID in NSPs (Aitken, Kerger, & Crofts, 2002), patients in a primary care clinic with certified methadone prescribers (Cullen et al, 2006), patients in specialty addiction treatment clinics and prison (Craine et al, 2014; Hickman et al, 2008), patients in a mobile medical clinic (Morano et al, 2014), and individuals with co-occurring substance use and serious psychiatric disorders in community mental health programs (Slade et al, 2013). The interventions described include free counseling and testing (Aitken et al, 2002), point-of-care testing (Morano et al, 2014), streamlined screen-test-immunize-reduce risk-refer protocols (Slade et al, 2013), dried blood spot testing (Craine et al, 2014; Hickman et al, 2008), and provider education with nursing support (Cullen et al, 2006). Programs were found to be generally effective at identifying new cases of chronic HCV and cost-effective when compared to treatment-as-usual, though often they required ancillary structural support to increase testing rates.…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 6 screening-related interventions (Table 1) demonstrate high rates of uptake and case-finding when interventions target high-risk individuals in specific settings, including PWID in NSPs (Aitken, Kerger, & Crofts, 2002), patients in a primary care clinic with certified methadone prescribers (Cullen et al, 2006), patients in specialty addiction treatment clinics and prison (Craine et al, 2014; Hickman et al, 2008), patients in a mobile medical clinic (Morano et al, 2014), and individuals with co-occurring substance use and serious psychiatric disorders in community mental health programs (Slade et al, 2013). The interventions described include free counseling and testing (Aitken et al, 2002), point-of-care testing (Morano et al, 2014), streamlined screen-test-immunize-reduce risk-refer protocols (Slade et al, 2013), dried blood spot testing (Craine et al, 2014; Hickman et al, 2008), and provider education with nursing support (Cullen et al, 2006). Programs were found to be generally effective at identifying new cases of chronic HCV and cost-effective when compared to treatment-as-usual, though often they required ancillary structural support to increase testing rates.…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
“…These studies demonstrated that patients with ongoing drug use and psychiatric comorbidity-- those traditionally excluded from systems of care-- can be effectively linked to care from and sometimes treated within these settings (Bruce et al, 2012; Jack, Willott, Manners, Varnam, & Thomson, 2009; McAllister et al, 2014; Morano et al, 2014; Newman et al, 2013; Seidenberg et al, 2013). One study implemented an integrated, multidisciplinary medical group visit to integrate care (Ho et al, 2013).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was based on previously validated studies in populations of homeless and tested in a pilot study [11, 1722]. Antibodies to HCV (anti-HCV) were detected by using rapid tests on capillary blood collected by finger-stick, as recommended by the World Health Organization and the Ministry of Health of Brazil for vulnerable populations [23, 24]. The test was interpreted ten minutes after the collection and the result was given to the patient during post-test counseling.…”
Section: Methodsmentioning
confidence: 99%
“…We focus specifically on experience of, and interventions to improve, phlebotomy in people with HCV. A recent systematic review examining interventions to improve treatment (Meyer et al 2015) only identified a single study related to phlebotomy, which was a comparison of standard phlebotomy and point of care testing for HCV screening (Morano et al 2014). We limited our search to studies reported in English.…”
Section: Limitationsmentioning
confidence: 99%